2014
DOI: 10.5812/ircmj.11794
|View full text |Cite
|
Sign up to set email alerts
|

Factor Structure of the Iranian Version of 12-Item General Health Questionnaire

Abstract: Background:The 12-Item General Health (GHQ-12) questionnaire is one of the most commonly used instruments in screening studies on mental health.Objectives:The current study aimed to examine the factor structure of the GHQ-12 questionnaire among the students in Iran.Materials and Methods:It was a cross-sectional study in which 428 university students were recruited and completed the GHQ-12. Reliability of the GHQ-12 was evaluated using the Cronbach's alpha and the split-half method by applying the Spearman-Brow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
25
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 44 publications
(47 reference statements)
4
25
1
Order By: Relevance
“…In the present study, the MIRT model with two factor showed an adequate fit for all indices. Our findings corroborate other studies that reported two dimensional structure including psychological distress and social dysfunction although they used CTT and CFA [14,13,5]. IRT-based models are really sparse in order to assess psychometric properties of GHQ-12.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…In the present study, the MIRT model with two factor showed an adequate fit for all indices. Our findings corroborate other studies that reported two dimensional structure including psychological distress and social dysfunction although they used CTT and CFA [14,13,5]. IRT-based models are really sparse in order to assess psychometric properties of GHQ-12.…”
Section: Discussionsupporting
confidence: 89%
“…The 12-items version of the questionnaire ,GHQ-12,6 was used broadly due to its relatively good psychometric properties and its brevity [3,4]. Further, the GHQ-12 is recommended by world health organization (WHO) as a wellvalidated and standard psychiatric screening instrument [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Originally, the GHQ-12 was developed as a unidimensional scale (Winefield, Goldney, Winefield & Tiggemann, 1989). However, alternative two-and three-factor models have also been proposed because these models may indicate different psychological problems encountered by individuals (Najarkolaei et al, 2014;Padrón et al, 2012). Werneke, Goldberg, Yalcin and Ustun (2000) showed that a two-factor model, consisting of 'Social Dysfunction' and 'Anxiety/Depression' factors, was supported.…”
Section: Introductionmentioning
confidence: 99%
“…The GHQ-12 has been translated into several languages worldwide [7, 9, 13, 1618, 20]. The aim of this study was to translate and test the reliability, validity and factor structure of GHQ-12 questionnaire for male tannery workers in India.…”
Section: Discussionmentioning
confidence: 99%